Non-covalent functionalization of carbon nano-onions with pyrene–BODIPY dyads for biological imaging1. Issue 62 (8th July 2015) - Bartelmess, Juergen; Frasconi, Marco; Balakrishnan, Preethi B.; Signorelli, Angelo; Echegoyen, Luis; Pellegrino, Teresa; Giordani, Silvia
<x xml:space="preserve">Abstract</x> We report a novel approach based on non-covalent interactions for the functionalization of carbon nano-onions (CNOs) with fluorophores.